2016
DOI: 10.1016/j.solidstatesciences.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of niobium based oxynitride nanosheets by exfoliation of Ruddlesden-Popper phase precursor

Abstract: To cite this version:Rietveld refinement of X-ray powder diffraction data in space group P4/mmm and considering a two-phase mixture, due to the difference in the degree of hydration, with a = 3.894(2) Å and c = 17.90(8) Å for the most hydrated phase and a = 3.927(6) and c = 17.09 (2) for the less one. Optical band gaps were measured by diffuse reflectance UV-Vis indicating a red shift of Eg to the visible region. The oxynitride layered perovskite was then protonated and exfoliated into nanosheets. TEM images a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Mallouk et al first showed that the Dion–Jacobson (D–J) phase oxides RbLaNb 2 O 7 and RbCa 2 Nb 3 O 10 could be transformed topochemically into Ruddlesden–Popper (R–P) phase oxynitrides Rb 1+ x LaNb 2 O 7– x N x · y H 2 O and Rb 1+ x Ca 2 NB 3 O 10– x N x · y H 2 O by nitridation of the oxide precursors with the aid of alkaline metal carbonates . Similar D–J to R–P topochemical conversions have been reported using KCa 2 Nb 3 O 10 and RbNdNb 2 O 7 , which were converted into K 1+ x Ca 2 Nb 3 O 10– x N x and Rb 2 NdNb 2 O 6 N, respectively. Recently, this topochemical method has been applied to the synthesis of Ta 5+ -based layered oxynitrides. , For example, K 2 LaTa 2 O 6 N·1.6H 2 O is an R–P phase layered oxynitride that functions as a visible-light-driven photocatalyst for H 2 evolution .…”
Section: Introductionmentioning
confidence: 99%
“…Mallouk et al first showed that the Dion–Jacobson (D–J) phase oxides RbLaNb 2 O 7 and RbCa 2 Nb 3 O 10 could be transformed topochemically into Ruddlesden–Popper (R–P) phase oxynitrides Rb 1+ x LaNb 2 O 7– x N x · y H 2 O and Rb 1+ x Ca 2 NB 3 O 10– x N x · y H 2 O by nitridation of the oxide precursors with the aid of alkaline metal carbonates . Similar D–J to R–P topochemical conversions have been reported using KCa 2 Nb 3 O 10 and RbNdNb 2 O 7 , which were converted into K 1+ x Ca 2 Nb 3 O 10– x N x and Rb 2 NdNb 2 O 6 N, respectively. Recently, this topochemical method has been applied to the synthesis of Ta 5+ -based layered oxynitrides. , For example, K 2 LaTa 2 O 6 N·1.6H 2 O is an R–P phase layered oxynitride that functions as a visible-light-driven photocatalyst for H 2 evolution .…”
Section: Introductionmentioning
confidence: 99%
“…There are two distinct crystallographic positions for the transition metals, two equivalent octahedra (Oct1) constituting the slab edges while the other one [2]. No significant morphological changes were observed for the synthesized materials, as evidenced by SEM results (SD-03) and large surfaces assigned to (0 1 0) planes were observed [13]. Stoichiometry of the samples was confirmed by SEM-EDXS (Table 1).…”
Section: Computational Detailsmentioning
confidence: 85%
“…Mallouk et al have reported that thermal ammonolysis of Dion–Jacobson oxides (e.g., RbCa 2 Nb 3 O 10 and RbLaNb 2 O 7 ) in the presence of Rb 2 CO 3 resulted in the formation of Ruddlesden–Popper phases of Rb 1+ x Ca 2 Nb 3 O 10– x N x · y H 2 O and Rb 1+ x LaNb 2 O 7– x N x · y H 2 O . Follow-up studies have shown that a similar topochemical conversion was possible for KCa 2 Nb 3 O 10 and RbNdNb 2 O 7 to yield K 1+ x Ca 2 Nb 3 O 10– x N x and Rb 2 NdNb 2 O 6 N, respectively. We have recently confirmed the adoptability of this topochemical approach to synthesize a new layered oxynitride, K 2 LaTa 2 O 6 N·1.6H 2 O, which consists of double-layer perovskite slabs interleaved with K + ions and hydrated water molecules .…”
Section: Introductionmentioning
confidence: 95%